Complete Linux training course to get your dream IT job. (Packt Publishing, 2022)
The best Linux administration course that prepares you for corporate jobs and for RHCSA, RHCE, LFCS, CLNP certifications About This Video Gain advanced Linux systems administration skills Understand Linux fundamentals and concepts Prepare for your Redhat Certified System Administrator (RHCSA - EX200) In Detail Linux is the number one operating system in the corporate world. It is a popular open-source operating system that is easy to use and highly secure. If you want to start your career in Linux and have little or no knowledge of Linux, then this course is for you. In this course, you will master Linux installation, configuration, administration, troubleshooting, the command line, OS tools, and much more. We have included resume and interview workshops that will help you get your dream IT job. This course will also help significantly in passing your RHCSA, RHCE, LFCS, and CompTIA Linux+ certification exams. By the end of this course, you will be a professional Linux administrator, be able to apply for Linux jobs and to take the EX-200 exam, and become a Redhat Certified System Administrator (RHCSA - EX200). Audience This course is designed for people who want to start a career in Linux, those who want to become a RedHat Certified System Administrator (RHCSA EX-200), and anyone keen to master Linux command-line skills.